Characterization of the complete mitochondrial genome of Lepus comus, the endemic Lepus in China. Issue 2 (3rd July 2019) - Huang, Jing; Lin, Wang; Wu, Dandan; Cai, Lifeng; Wang, Xiumei; Huang, Jianhui
Abstract: Lepus comu s is the endemic species in China and has been listed on the IUCN Red List in 2013. In this study, we undertook and obtained the complete Lepus comu s mitochondrial genome. The circular mitochondrial genome sequence is 17, 534 bp in size, containing 13 protein-coding genes (PCGs), 21 transfer RNA (tRNA) genes, 2 ribosome RNA (rRNA) genes and a longer D-loop region of 2, 610 bp in length. The base composition of the mtDNA is as follows: 31.5% of A, 29.8% of T, 29.8% of C and 13.3% of G, with a total G + C content of the mtDNA 38.7% and A + T of 61.3%. The phylogenetic Maximum-Likelihood (ML) tree was constructed to validate the taxonomic status of Lepus comu s, exhibiting the closest relationship with Lepus tibetanus . The study of the complete Lepus comu s mitochondrial genome can provide a reference taxonomic relationships and more basic data for future.